Language Errors in Arabic Speaking Skill: A qualitative Case Study of Indonesian Madrasah School - Nova Ariyanti; Miftahul Huda; Ma'rifatul Munjiah (Abjadia : International Journal of Education, 2026)
This study aims to identify language errors in Arabic speaking skill (Maharah Kalam) among students at Madrasah Aliyah Muhammadiyah 1 Plus Malang and to determine the factors influencing these errors. A qualitative method with a case study approach was employed, with data collected through observation, interviews, and documentation. Data analysis consisted of three concurrent stages: data reduction, data display, and conclusion drawing. The findings of this research indicate that students at Madrasah Aliyah Muhammadiyah 1 Plus Malang continue to encounter several challenges in developing their Arabic speaking skills. The difficulties identified include mistakes in pronunciation, inappropriate vocabulary choice, inaccuracies in linguistic structure, sentence construction issues, lack of fluency, and errors related to content and meaning. Among these, pronunciation mistakes were found to be the most frequent, followed by structural and grammatical inaccuracies. These problems are mainly caused by the students’ limited mastery of linguistic components and the absence of a supportive environment for active language practice. Moreover, variations in students’ cognitive abilities also contribute to differences in their proficiency levels in Arabic speaking skills.